2014
DOI: 10.1631/jzus.b1300141
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics of borneol in cerebral ischemia-reperfusion and sham-operated rats

Abstract: These results suggest that the pathological damages of ischemia-reperfusion have a significant impact on the pharmacokinetic traits of borneol and that there are some components in XNJ inhibiting the absorption of borneol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…These data indicated that some ingredients in GSC but not eugenol could suppress resorption and reduce the bioavailability of bicyclic monoterpenes. It was reported that the absorption of borneol was inhibited and elimination time was increased in another Chinese formula Xingnaojing , which were similar to our results. An enzyme experiment in vitro indicated that CYP3A4 was one of the main enzymes involved in the metabolism of borneol and isoborneol.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These data indicated that some ingredients in GSC but not eugenol could suppress resorption and reduce the bioavailability of bicyclic monoterpenes. It was reported that the absorption of borneol was inhibited and elimination time was increased in another Chinese formula Xingnaojing , which were similar to our results. An enzyme experiment in vitro indicated that CYP3A4 was one of the main enzymes involved in the metabolism of borneol and isoborneol.…”
Section: Resultssupporting
confidence: 92%
“…Under the two different delivery methods of oral and intravenous injection, the pharmacokinetics of eugenol in rats were examined by means of LC–MS/MS method . Some methods based on GC or GC–MS have been reported for the detection of bicyclic monoterpenes in biological samples . However, there is still no method established for simultaneous determination of the four ingredients mentioned above for pharmacokinetic investigations.…”
Section: Introductionmentioning
confidence: 99%
“…For investigating the role of (+)-borneol in permanent cerebral ischemia, 45 male Sprague-Dawley rats were randomly divided into the sham group, the vehicle-treated group and the (+)-borneol-treated groups (1.0 mg/kg), with 15 rats in each group. The terminal half-life (t 1/2 ) of borneol was 2 h following cerebral ischemia-reperfusion [ 16 ] . We subjected the rats to pMCAO and administered drugs by tail intravenous injection 2 hours and 5 hours after pMCAO, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…But none of them was administrated intranasally. Xu [19] studied the pharmacokinetics of borneol in cerebral ischemia-reperfusion and sham-operated rats after oral administration. Significant rise were observed on AUC and C max , but there were no differences between two groups on T 1/2 .…”
Section: Discussionmentioning
confidence: 99%